Hubungan Tingkat Pengetahuan Pasien Dengan Kadar Gula Darah Pada Pasien Diabetes Melitus - Dia Rejeki Utami; Andi Ernawati Manuntungi (Barongko: Jurnal Ilmu Kesehatan, 2026)
Diabetes Mellitus is a chronic disease characterized by elevated blood sugar levels due to impaired insulin secretion or function. Blood sugar control is significantly influenced by patient behavior in managing the disease, one of which is the patient's level of knowledge. Good knowledge is expected to encourage patients to adopt a healthy lifestyle and adhere to treatment. This study aims to determine the relationship between patient knowledge and blood sugar levels in patients with Diabetes Mellitus. This study used a quantitative method with an analytical design and a cross-sectional approach. The study sample was patients with Diabetes Mellitus undergoing treatment at health care facility X. Data were collected using a knowledge questionnaire and blood sugar level results, then analyzed using the Chi-Square test. The results showed a significant relationship between patient knowledge and blood sugar levels (p < 0.05).